Hydrogen storage potential in underground coal gasification cavities: a MD simulation of hydrogen adsorption and desorption behavior in coal nanopores - Tao, Liru; Feng, Hongye; Ju, Yiwen; Zhu, Hongjian; Wei, Zixiang (Frontiers in Earth Science, 2025)
Underground hydrogen storage (UHS) in geological formations presents a viable option for long-term, large-scale H2 storage. A physical coal model was constructed based on experimental tests and a MD simulation was used to investigate the potential of UHS in underground coal gasification (UCG) cavities. We investigated H2 behavior under various conditions, including temperatures ranging from 278.15 to 348.15 K, pressures in the range of 5–20 MPa, pore sizes ranging from 1 to 20 nm, and varying water content. We also examined the competitive adsorption dynamics of H2 in the presence of CH4 and CO2. The findings indicate that the optimal UHS conditions for pure H2 involve low temperatures and high pressures. We found that coal nanopores larger than 7.5 nm optimize H2 diffusion. Additionally, higher water content creates barriers to hydrogen diffusion due to water molecule clusters on coal surfaces. The preferential adsorption of CO2 and CH4 over H2 reduces H2-coal interactions. This work provides a significant understanding of the microscopic behaviors of hydrogen in coal nanopores at UCG cavity boundaries under various environmental factors. It also confirms the feasibility of underground hydrogen storage (UHS) in UCG cavities.